2016
DOI: 10.1002/jid.3267
|View full text |Cite
|
Sign up to set email alerts
|

Learn to Play and Play to Learn: Evaluation of the One Laptop per Child Program in Costa Rica

Abstract: The One Laptop Per Child (OLPC) initiative is one of the worldˈs most popular interventions aiming to reduce the Information and Communication Technologies (ICTs) digital divide. Costa Rica introduced its first OLPC program in February 2012. In collaboration with the Quirós Tanzi Foundation (Foundation), implementing the program, baseline and post-intervention information was collected from a set of 15 primary schools that were selected to be treated, and from 19 primary schools that served as a comparison gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 20 publications
2
2
0
Order By: Relevance
“…This requires regulation by internet providers in addition to supervision by guardians or adults. The results are consistent with previous studies (Malamud et al 2019;Cristia, Czerwonko, and Garofalo 2010;Malamud and Pop-Eleches 2011;Meza-Cordero 2017;Bet, Cristia, and Ibarrarán 2014) showing that increase in access to ICT increases digital skills.…”
Section: Quasi-experimental Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This requires regulation by internet providers in addition to supervision by guardians or adults. The results are consistent with previous studies (Malamud et al 2019;Cristia, Czerwonko, and Garofalo 2010;Malamud and Pop-Eleches 2011;Meza-Cordero 2017;Bet, Cristia, and Ibarrarán 2014) showing that increase in access to ICT increases digital skills.…”
Section: Quasi-experimental Resultssupporting
confidence: 93%
“…In Table 3, Panel B, Columns 2 and 3, the study finds no gendered treatment effect on school attendance. On the broader study on ICT and education outcomes, the findings on school attendance are contrary to those of Banerjee et al (2007) and Kho, Lakdawala, and Nakasone (2018) who found that investment in ICT infrastructure increases education outcomes; but are in line with previous studies (Angrist and Lavy 2002;Malamud et al 2019;Cristia, Czerwonko, and Garofalo 2010;Malamud and Pop-Eleches 2011;Meza-Cordero 2017;Bet, Cristia, and Ibarrarán 2014) that found that investment in ICT infrastructure has limited impacts on education outcomes.…”
Section: Effects On School Attendancesupporting
confidence: 66%
“…In one of the early studies of Avancemos , Mata and Hernández (2015) found that after its first year of implementation, the program led to a reduction of school dropout rates between 10% and 16%, and an increase in school reinsertion rates of 77%. Meza‐Cordero (2014) conducted an evaluation of Avancemos after the first 3 years of implementation and found that the intervention led to an increase in school completion of 0.62 years, with no effects on the number of hours worked.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The author argues that the lack of complementary infrastructure, teacher support, and maintenance hinders the effectiveness of the program and is cause of OLPC failure. For the case of the OLPC intervention in Costa Rica, Meza-Cordero (2017) showed that after one year of laptop provision and adequate support structure, students increased their computer usage both in school and at home, allocated less time to homework and outdoor activities, and did not increase their school performance.…”
Section: Literature Reviewmentioning
confidence: 99%